Exploring the knowledge of social media platforms among higher education institute students’ of Rangpur, Bangladesh - Prodhan, Md. Tabiur Rahman; Islam, Md. Nazrul; Hossain, Md. Sajjat (Recent Research in Science and Technology, 2020)
Social media (SM) is one of the best indicators of the technological era. Nowadays people are witnessing the rapid increase of SM in almost every field of our lives from education to politics, society, and economics. It attracts all ages of people. Especially students show an intense interest in social media. The purpose of the study was to know the most preferred SM and the using pattern knowledgeability of respondents regarding various social media platforms (SMPs). A questionnaire-based survey was conducted over 100 students (60 males and 40 females) who were selected randomly from two largest universities in Rangpur, northern part of Bangladesh, studying in undergraduate and postgraduate programs in 2019 between ages 18 and 26. 95% of the respondents used different social media platforms where the top preferred social media platforms are Facebook (88%), YouTube (81%), and IMO (45%). The mean values of the respondents’ using pattern knowledgeability level were between 4.46 and 1.88, with standard deviations ranging from 1.10 to 1.83. Most of the respondents have enough using pattern knowledgeability of being a user of Facebook with a wide range of mean scores in both the variables. Respondents have less using pattern knowledgeability of being a user of Viber with a tight range of mean scores in both the variables. All the dependent variables (features), except one (r-value 0.253), showed positive and significant correlations with the usage period where both the features of Twitter have the highest positive significance (r-value 0.945, 0.941 respectively). These scores were significant at p<0.05 level of probability.